2007
DOI: 10.1007/s00726-007-0523-2
|View full text |Cite
|
Sign up to set email alerts
|

Antizyme and antizyme inhibitor activities influence cellular responses to polyamine analogs

Abstract: Close structural analogs of spermidine and spermine, polyamine mimetics, are potential chemotheraputic agents as they depress cellular polyamines required for tumor growth. Specific mimetic analogs stimulate synthesis of the regulatory protein antizyme (AZ), which not only inactivates the initial enzyme in polyamine biosynthesis but also inhibits cellular uptake of polyamines. The role of AZ induction in influencing cellular uptake of representative analogs was investigated using three analogs produced by Cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…This greater perturbation of polyamine pools in the non-small cell lines is consistent with previous analogue studies and is most likely the result of the significantly greater increase in polyamine catabolism induced by analogue treatment of the non-small cell lines as compared to the small cell lines, which demonstrate little or no induction of either SSAT or SMO in response to analogue treatment [11,12,25,54]. Although analogue treatment of all cell types reduced ODC activity, most likely due to an increase in ODC antizyme production as previously demonstrated by Mitchell and colleagues [36,37], it is clear that the combination of decreased polyamine synthesis and increased polyamine catabolism leads to the greatest depletion of intracellular polyamines. This phenotypic difference in total polyamine depletion may have more significance in vivo than in vitro, since in the in vivo setting the availability of circulating polyamines may be able to overcome the simple down regulation of ODC exhibited by the small cell lung cancer phenotype.…”
Section: Discussionmentioning
confidence: 56%
“…This greater perturbation of polyamine pools in the non-small cell lines is consistent with previous analogue studies and is most likely the result of the significantly greater increase in polyamine catabolism induced by analogue treatment of the non-small cell lines as compared to the small cell lines, which demonstrate little or no induction of either SSAT or SMO in response to analogue treatment [11,12,25,54]. Although analogue treatment of all cell types reduced ODC activity, most likely due to an increase in ODC antizyme production as previously demonstrated by Mitchell and colleagues [36,37], it is clear that the combination of decreased polyamine synthesis and increased polyamine catabolism leads to the greatest depletion of intracellular polyamines. This phenotypic difference in total polyamine depletion may have more significance in vivo than in vitro, since in the in vivo setting the availability of circulating polyamines may be able to overcome the simple down regulation of ODC exhibited by the small cell lung cancer phenotype.…”
Section: Discussionmentioning
confidence: 56%
“…This uptake activity suggested the therapeutic use of structural analogs of polyamines that cross the plasma membrane through the polyamine uptake system. While some analogs exert their cytotoxic effect by negating the function of the physiological polyamines, others that are usually the most effective analogs also stimulate antizyme production [115]. Since the effectiveness of such toxic polyamine analogs also depends on the level of antizyme inhibitor in the treated cells, an additional challenge will be to match the optimal treatment (synthesis inhibitors vs polyamine analogs or their combination) to the composition of the molecular players in the treated cells.…”
Section: Discussionmentioning
confidence: 98%
“…AZ also feedback inhibits the uptake of polyamines by cells. Mitchell et al, 2007 showed that polyamine analogues induced AZ1 and also decreased their own uptake and the uptake of other polyamines (Mitchell et al 2007). Thus, polyamines can regulate their own synthesis and levels via AZ1.…”
Section: Discussionmentioning
confidence: 99%